Tax Factors of Economic Dynamics: Analysis Based on the Modified IS–LM Model - Merkulova, Tamara; Bitkova, Tetiana; Nikolaeva, Olena; Stetsenko, Tetiana (Dr. Viktor Koval, 2026)
Background. Taxation is a fundamental instrument of macroeconomic policy, and its influence across various economic and social domains remains one of the most significant subjects of research. Particular attention is devoted to examining the capacity of taxation to regulate economic cycles, shape dynamic processes, and affect the market equilibrium of an economic system. The development of dynamic models of economic equilibrium incorporating endogenous tax factors as a methodological foundation for macroeconomic policy constitutes a significant research objective. Purpose. This study examines the impact of taxation indicators on macroeconomic dynamics within the dynamic IS–LM framework, incorporating endogenous taxes, mathematical and simulation analyses of oscillatory conditions, and assessment of the influence of tax variables on dynamic regimes. Findings. This study presents a modified IS-LM model with endogenous taxes, demonstrating the potential influence of taxation on the type of dynamics of economic systems, particularly the exit from the fluctuation zone and vice versa. The theoretical analysis of the model consists of two stages: 1) mathematical analysis of the tax parameter’s influence on the type of dynamics of the economic system, and 2) simulation analysis based on the System Dynamics concept. As a result of the first stage, mathematically justified bounds for the tax rate were obtained, which determine its potential (in combination with other parameters) to reflect the diversity of economic systems. In particular, it is shown that for certain values of other model parameters, the transition from fluctuations is possible with both a high tax burden (e.g. above 50%) and a low one (e.g. 20% or below). Implications. The simulation model developed using the System Dynamics concept demonstrates the possibility of analysing feedback loops that include key variables of the model, revealing reinforcing or balancing mechanisms within closed chains of endogenous variables, and of multivariate calculations and analysis of the impact of various combinations of exogenous parameters on selected response functions (GDP or Interest rate) with the subsequent development of regression meta-models.